CaFu MOF as an efficient adsorbent for simultaneous removal of imidacloprid pesticide and cadmium ions from wastewater. (June 2021) - Singh, Sandeep; Kaushal, Sandeep; Kaur, Jasmeen; Kaur, Gurmeet; Mittal, Susheel Kumar; Singh, Prit Pal
Abstract: Heavy metal ions and pesticides are the noteworthy toxic substances which must be removed from contaminated water for safeguarding public health. The higher levels of these substances in natural water may adversely affect the human health, climate and the eco-framework. The adsorptive removal of hazardous constituents employing metal organic frameworks has drawn considerable attention of researchers during the last decade. From this point of view, single crystal of calcium fumarate [Ca(C4 H4 O4 )1.5 (H2 O)(CH3 OH)2 ] has been developed and analyzed by single crystal X-ray crystallography which confirmed the formation of 3-D metal organic frameworks (MOFs). The synthesized MOFs was employed for simultaneous adsorptive removal of imidacloprid, a high consumption pesticide, and highly toxic Cd (II) from aqua ecosystem. The effect of variation in experimental conditions such as solution pH, adsorbent dosage, contact time, initial concentration and temperature on adsorption was systematically evaluated. Both the imidacloprid and Cd(II) exhibited maximum adsorption at pH 6.5 and 7.8, respectively. The equilibrium empirical data was fitted into Langmuir, Freundlich and Temkin isotherms. The adsorption capacity of CaFu MOFs was observed to be 467.23 and 781.2 mg g −1 for imidacloprid and cadmium ions, respectively. The adsorbed pollutants were desorbed from the adsorbent using dilute HCl, and the material was reused for five adsorption-desorption cycles without any appreciable loss of adsorption capacity. Therefore, the 3-D CaFu MOFs could be utilized as a novel material for adsorptive removal of imidacloprid pesticide as well as Cd (II) from wastewater. Graphical abstract: Image 1 Highlights: 3-D CaFu MOF single crystal synthesized using solvothermal method. CaFu MOF as highly selective adsorbent for imidaclopid and Cd (II) ions. The MOF as an adsorbent for simultaneous removal of imidacloprid and Cd (II) ions. Adsorption of both the pollutants on CaFu follow pseudo-first-order model.